Operation Management Scenarios of Medium Voltage Distribution 20 kV with PV Rooftop Penetration - Medina, Intan Aprilia; Giriantari, I. A. Dwi; Ariastina, W. G. (Journal of Electrical, Electronics and Informatics, 2022)
The availability of renewable energy in various sectors certainly needs to be improved, one of which is Solar Power Plant  or PV. The province of Bali has a Solar Power Plant (PV) development target of 108 MW by 2025. The Solar Power Plant target has been stated in the RUEN (National Energy General Plan) policy. Efforts made by the Province of Bali to support and to realize the RUEN target are in the Bali Governor Regulation (Pergub) No. 45 of 2019 concerning "Clean Energy Bali". One of the areas in Bali that can be developed as a PV development is Nusa Dua area. In this area, the integration of conventional grid systems and renewable energy (PV Rooftop) can be carried out. In this journal, the author proposes several scenarios that are expected to be considered in planning the integration of a 20 kV grid system with renewable energy power plants. Some of these ideas are the integration of 25%, 50%, and 100% of PLTS capacity in meeting electrical energy needs. The purpose of the scenario is to find out the direction of the flow supplied by the PV, and to know whether the grid will remain stable or not if disturbance occurs.